Solidarity and Bureaucratic Negotiations: Public Value Production in The Management of Zakat Baznas Karanganyar Regency - Zidan Muhamad Putranto,; Faizatul Ansoriyah, (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
Zakat as the fifth pillar of Islam is a religious instrument to increase social justice and solve economic problems for the Muslim population. This study aims to explore the management of zakat distribution in Karanganyar Regency from the perspective of public value focusing on the Karanganyar Makmur program organized by BAZNAS Karanganyar. This study uses a descriptive qualitative approach with primary data collection techniques in the form of interviews with three mustahik and one BAZNAS Karanganyar administrator through open-ended questions. Secondary data sources in this study were obtained through various published data sources, such as BAZNAS Karanganyar publication documents, other government website publications , and laws and regulations. The results of the study show that zakat is distributed equally to all mustahik groups who are entitled by paying attention to specific needs. BAZNAS Karanganyar ensures that the distribution of zakat is distributed to all reaches in Karanganyar Regency. In addition, the management of zakat distribution with economic empowerment through productive programs is carried out to reduce poverty and improve the welfare of mustahik. Therefore, the management of zakat distribution by BAZNAS Karanganyar creates public value through equity, justice, regionality, and welfare. The management of zakat distribution by BAZNAS Karanganyar creates public value by reducing social gaps, empowering communities, and supporting the vision of local governments in poverty alleviation.